2016
DOI: 10.1007/s12144-016-9537-9
|View full text |Cite
|
Sign up to set email alerts
|

The Need to Present a Perfect Body Image: Development of a New Measure of Perfectionistic Self-Presentation

Abstract: Perfectionistic self-presentation is linked to different clinical conditions and especially to eating disorders. In fact, the role that the drive to reach "perfection" and display it to others plays on eating and body image-related symptoms has long been the target of theoretical and empirical interest. However, an instrument that specifically assessed the need to present a perfect body image to others did not exist. The current study presents the development and validation of the Perfectionistic Self-Presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Furthermore, our results are in line with previous literature which revealed that submissiveness is associated with higher levels of disordered eating (e.g., Katzman, 1985; Troop & Treasure, 1997). Also, our findings seem to be in accordance with previous research (Ferreira, Duarte et al, 2015, manuscript submitted for publication; Ferreira, Trindade et al, 2015) by suggesting body-image related perfectionistic self-presentation as a maladaptive strategy, which may be linked to the adoption of disordered eating attitudes and behaviors. Specifically, this study seems to extend previous knowledge since it revealed that perfectionistic self-presentation focused on body image acts as a mediator mechanism between submissiveness and eating psychopathology.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our results are in line with previous literature which revealed that submissiveness is associated with higher levels of disordered eating (e.g., Katzman, 1985; Troop & Treasure, 1997). Also, our findings seem to be in accordance with previous research (Ferreira, Duarte et al, 2015, manuscript submitted for publication; Ferreira, Trindade et al, 2015) by suggesting body-image related perfectionistic self-presentation as a maladaptive strategy, which may be linked to the adoption of disordered eating attitudes and behaviors. Specifically, this study seems to extend previous knowledge since it revealed that perfectionistic self-presentation focused on body image acts as a mediator mechanism between submissiveness and eating psychopathology.…”
Section: Discussionsupporting
confidence: 93%
“…Given the historical relevance of the female body shape as a central domain in self and social evaluations (Gatward, 2007), the majority of women tend to invest in this dimension with the purpose of promoting attractiveness in the minds of others (Gilbert et al, 1995). However, such investment may demand extreme self-monitoring patterns and control over one’s body weight, shape, and eating behaviors, in order to reach the “perfect” physical appearance (Ferreira, Trindade, & Ornelas, 2015). The need to present one’s physical appearance in a perfectionistic way, conceptualized as body image-related perfectionistic self-presentation, has been associated with proneness to eating disorders, particularly to the increase of body dissatisfaction and drive for thinness (Ferreira, Duarte, Pinto-Gouveia, & Lopes, 2015, manuscript submitted for publication; Ferreira et al, 2015).…”
mentioning
confidence: 99%
“…Since body image is an important issue in sports, especially in aesthetic sports, the need to present a perfect physical appearance seems to be particularly relevant in this context. According to Ferreira, Marta-Simões, and Trindade ( 2016 ), body image-related perfectionist self-presentation (defined as the need to present a perfect physical appearance to others) is positively linked with depressive symptomatology (Marta-Simões & Ferreira, 2016 ) and with disordered eating (Ferreira et al, 2016 ; Ferreira, Duarte, Pinto-Gouveia, & Lopes, 2018a , Ferreira, Mendes, & Trindade, 2018b ; Ferreira, Ornelas, & Trindade, 2015a , Ferreira, Trindade, Duarte, & Pinto-Gouveia, 2015b ). Nevertheless, body image-related perfectionist self-presentation remains unexplored in aesthetic athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The same is to say that body shape is a dimension particularly used to obtain social attention and acceptance by others (Gilbert et al, 1995; Troop, Allan, Treasure, & Katzman, 2003). For that reason, body shape is currently overvalued in women’s social comparisons and in the establishment of their rank within the group (Buote et al, 2011; Ferreira, Pinto-Gouveia, & Duarte, 2013). Moreover, unfavorable comparisons based on physical appearance tend to trigger feelings of inferiority and unattractiveness, and, consequently, high levels of shame (Goss & Gilbert, 2002).…”
mentioning
confidence: 99%
“…More specifically, studies have highlighted the positive relationship between strive for perfection, body dissatisfaction, and disordered eating (e.g., Hewitt, Flett, & Ediger, 1995; McGee, Hewitt, Sherry, Parkin, & Flett, 2005). Furthermore, recent research demonstrated that perfectionistic self-presentation specifically related to body image is particularly present in women and is linked to increased body dissatisfaction and drive for thinness (Ferreira, Duarte, Pinto-Gouveia, & Lopes, 2013). However, although promising, studies in this particular domain are yet scarce.…”
mentioning
confidence: 99%